2019
DOI: 10.3390/molecules24203733
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Polysaccharides in Psoralea corylifolia L and anti-A549 Lung Cancer Cells Activity In Vitro

Abstract: Two novel water soluble heteroglycan (PCp-I and PCp-II) with anti-A549 lung cancer cells activity were isolated from Psoralea corylifolia L. Their average molecular weights were 2.721 × 104 and 2.850 × 104. PCp-I and PCp-II had the same monosaccharide composition, but their molar ratios were different. Based on methylation and NMR spectroscopy, the part structure of PCp-I was identified. The results of scanning electron microscope (SEM) showed that PCp-I had an irregular porous structure and PCp-II was flaky a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
(48 reference statements)
1
9
0
Order By: Relevance
“… 2015 ; Yin et al. 2019 ). Combination therapy of different drugs might induce adverse interaction that leads to treatment failure and even toxicity (Hu et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2015 ; Yin et al. 2019 ). Combination therapy of different drugs might induce adverse interaction that leads to treatment failure and even toxicity (Hu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Co-administration of various drugs possesses multi-target and multi-level function characteristics, especially in intractable diseases with complications (Huang et al 2018). Pachymic acid and bavachin are major active ingredients of P. cocos and P. corylifolia, respectively, which are commonly combined in the therapeutic prescription of lung cancer due to their similar anti-tumor effect (Ling et al 2010;Ma et al 2015;Yin et al 2019). Combination therapy of different drugs might induce adverse interaction that leads to treatment failure and even toxicity (Hu et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCp-I was composed of rhamnose, arabinose, xylose, mannose, glucose and galactose. 2 Polysaccharide has a wide range of biological activities, such as immunomodulation, [3][4][5] anti-tumor, 6 anti-oxidation 7,8 and anti-virus. 9 Immunomodulatory activity is recognized as the most important effective biological effects of polysaccharide and some scholars have found that the structure of polysaccharide including the monosaccharide composition, glycosidic-linkage position, molecular weight and branching are closely Activation of RAW264.7 cells by PCp-I, a polysaccharide from Psoralea corylifolia L, through NF-κB/MAPK signalling pathway related to its immunostimulatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…11 Inhibiting effect of PCp-I on the A549 lung cancer cells was confirmed in our previous research while the immune activity has not been studied. 2 The main targets responding to immune molecules are monocytes, macrophages and neutrophils. 11 In this research, the mouse macrophage RAW264.7 was selected to study the immunomodulatory effects of PCp-I.…”
Section: Introductionmentioning
confidence: 99%